2017
DOI: 10.1007/s10396-017-0792-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic identification of pump twin by dual-gate Doppler in a monochorionic-triamniotic triplet twin reversed arterial perfusion sequence before preventative radiofrequency ablation: a case report

Abstract: We performed a dual-gate Doppler examination for a twin reversed arterial perfusion (TRAP) sequence in a monochorionic-triamniotic triplet pregnancy at 16 weeks of gestation and were able to identify the pump twin by arterial pulse rate synchronicity. We performed radiofrequency ablation to coagulate blood flow in the acardius at 16 weeks of gestation without any postoperative complication. At 29 weeks of gestation, we performed a cesarean section due to preterm rupture of the membranes and the patient deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…This is the first report on two liveborn infants delivered in term after successful RFA for monochorionic-triamniotic triplet pregnancy with TRAP sequence. There were two similar reports; however, the liveborn infants were preterm [4, 5]. In the current case, we succeeded in complete blood flow cessation with a single puncture on the acardiac fetus stuck to the anterior uterine wall.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This is the first report on two liveborn infants delivered in term after successful RFA for monochorionic-triamniotic triplet pregnancy with TRAP sequence. There were two similar reports; however, the liveborn infants were preterm [4, 5]. In the current case, we succeeded in complete blood flow cessation with a single puncture on the acardiac fetus stuck to the anterior uterine wall.…”
Section: Discussionsupporting
confidence: 51%
“…Vascular anastomoses between triplets A and B were confirmed by Doppler ultrasound examination. Takahashi et al reported that pump fetus identification was possible using dual-gate Doppler (ARIETTA 70) [5]. Here, we could distinguish the pump fetus from the indirect pump fetus based on the different baseline FHRs, which had relatively few fluctuations during gestation.…”
Section: Discussionmentioning
confidence: 94%
“…2 7 16 +1 Fetoscopic laser surgery 28 +4 Two live infants (917 and 713 g), 12 wks NICU stay. 3 8 16 +3 Unknown 29 +3 Two live infants (1167 and 1237 g), NICU stay; one macerated acardiac fetus. 4 9 23 +4 In utero radiofrequency ablation 31 +5 Two live infants (1515 and 1275 g), 3 wks NICU stay; one macerated acardiac fetus.…”
Section: Gestational Age At Intervention (Wks)mentioning
confidence: 99%
“…Seventeen cases of monochorionic triplets with TRAP were identified in the literature (Table 2). 1 , 416 Radiofrequency ablation (RFA) was performed in 5 of these cases, intrafetal laser in 2 cases, fetoscopic laser surgery in 1 case and intrathoracic injection of 10% NaCl in 2 cases. All 10 cases where an interventional procedure had been performed had survival of one or both nonacardiac twins.…”
Section: Case Reportsmentioning
confidence: 99%